The Fulling-Davies-Unruh effect is mandatory: the proton's testimony - Matsas, GEA; Vanzella, DAT (World Scientific Publ Co Pte Ltd, 2002)
We discuss the decay of accelerated protons and illustrate how the Fulling-Davies-Unruh effect is indeed mandatory to maintain the consistency of standard Quantum Field Theory. The confidence level of the Fulling-Davies-Unruh effect must be the same as that of Quantum Field Theory itself.